Difficult to change? The differences between successful and not‐so‐successful participation in anger management groups. Issue 2 (1st November 2019) - Shepherd, Gary; Cant, Matthew
Abstract: Background: Although much is known about the importance of anger management programmes, little has been written on the self‐reported differences in experience between people who feel they have been successful and those who feel less successful in their change efforts. Research aim: This research aimed to explore the reported differences in experiences between men who had reduced their angry behaviours and men who had been less able to reduce their anger. Method: Phenomenological research was carried out using data from the weekly 'check‐in' process of six male participants enrolled on one of two 10‐week mindfulness‐based anger management programmes. The data were analysed using interpretative phenomenological analysis. Key Findings: Men who reported successfully lowering their anger developed an improved bodily awareness, the ability to calm other people down in tense situations and possessed a determination to continue the course 'homework' exercises. Men who reported less success seemed to be in 'emotionally stuck' states, found it difficult to change their perceptions of threatening situations and had problems continuing their homework practice. Conclusion: Men who struggle to manage their anger may have deeper developmental issues preventing them from changing their angry responses. The authors recommend that in order to help such men, new anger theory and practice be developed, informed by the notion of narcissism.